Cost effectiveness comparison of dutasteride and finasteride in patients with benign prostatic hyperplasia – The Markov model based on data from Montenegro - Vera, Dabanović; Kostić, Marina; Janković, Slobodan (Vojnosanitetski pregled, 2017)
Background/Aim. Benign prostatic hyperplasia (BPH) is one of the most common disease among males aging 50 years and more. The rise of the prevalence of BPH is related to aging, and since duration of life time period has the tendency of rising the prevalence of BPH will rise as costs of BPH treatment will and its influence on health economic budget. Dutasteride is a new drug similar to finasteride, inhibits enzyme testosterone 5-alpha reductase, diminish symptoms of BPH, reduce risk of the complications and increases quality of life in patients with BPH. But, the use of dutasteride is limited by its high costs. The aim of this study was to compare cost effectiveness of dutasteride and finasteride from the perspective of a purchaser of health care service (Republic Institute for Health Insuranse, Montenegro). Меthods. We constructed a Markov model to compare cost effectivenss of dutasteride and finasteride using data from the available pharmacoeconomic literature and data about socioeconomic sphere actual in Montenegro. A time horizon was estimated to be 20 years, with the duration of 1 year per one cycle. The discount rate was 3%. We performed Monte Carlo simulation for virtual cohort of 1,000 patients with BPH. Results. The total costs for one year treatment of BPH with dutasteride were estimated to be 6,458.00 € which was higher comparing with finasteride which were 6,088.56 €. The gain in quality adjusted life years (QALY) were higher with dutasteride (11.97 QALY ) than with finasteride (11.19 QALY). The results of our study indicate that treating BPH with dutasteride comparing to finasteride is a cost effective option since the value of incremental cost-effectiveness ratio (ICER) is 1,245.68 €/QALY which is below estimated threshold (1,350.00 € per one gained year of life). Conclusion. Dutasteride is a cost effective option for treating BPH comparing to finasteride. The results of this study provide new information for health care decision makers about treatment of BPH in socioeconomic environment which is actual both in Montenegro and other countries with a recent history of socioeconomic transition.
Keywords: economics; pharmaceutical; prostatic hyperplasia; 5-alpha-reductase inhibitors; cost-benefit analysis; montenegro